Labor revitalization global perspectives and new initiatives - Cornfield, Daniel B.; McCammon, Holly J., 1959- (Research in the sociology of work, 2003)
This work examines variations among nations in the wide array of initiatives labour unions and labour movements are taking to strengthen themselves and recruit new members. Moving beyond previous research on the factors leading to union decline, the international group of scholars who have contributed to this volume present a research agenda on the many initiatives unions are taking - and the different social, economic, and political challenges they face in several world regions, as labour movements endeavor to revitalize themselves. These revitalizing initiatives include changing labor leadership and membership organizing strategies; "social movement unionism"; broadening the range of services provided to union members; and pursuing political and legal reform that achieves freedom of association. The contemporary cases of labour revitalization in this volume have occurred in Australia, Brazil, Germany, Korea, Mexico, the Netherlands, the United Kingdom, the United States, and Venezuela. The research agenda presented here rests on the conceptualization of labour revitalization as "socially embedded action," or strategic action taken by labor unions to strengthen themselves by redefining their relationships with workers, employers and states. Each of the three parts of "Labor Revitalization" addresses labour's changing relationships with workers, employers, and states, respectively.